Love's enduring promise - Oke, Janette, 1935- (Minneapolis, Minn. : Bethany House, 2003)
Clark and Marty, now together after the deaths of their first mates, preside over a growing number of children in their prairie homestead.
"Newly edited and revised"--T.p. verso.
Sequel to: Love comes softly.
900
Accelerated Reader AR
Keywords: Davis family (Fictitious characters : Oke) -- Fiction; Married people -- Fiction; Women pioneers -- Fiction; Domestic fiction; Christian fiction